Relationship Between Maternal Employment and Empathy, Positivity, and Personality Traits of Adolescent Girls - Marzie Hashemi; Mahin Shekari-Bagheney (Journal of Client-centered Nursing Care, 2024)
Background: The shift towards increased workforce participation by women, especially mothers, has given rise to intriguing questions about the potential implications for their children’s development. This study contributes to this discourse by comparing adolescent girls’ positivity, empathy, and personality traits with regard to working and non-working mothers. Methods: This descriptive correlational study was carried out in Karaj City, Iran, in 2022. The subjects were 118 students aged 14-18 years from two separate high schools in an urban area recruited by multi-stage cluster random sampling. The sample was divided into two groups of students with working mothers (n=56) and non-working mothers (n=62). The data were collected using the Davis empathy questionnaire, positive psychotherapy inventory, Big Five questionnaire-children, and the researcher-made questionnaire on the mother’s employment status. The Pearson correlation coefficient, multivariate analysis of variance, the chi-square test, and the t-test were used for data analysis in SPSS software, version 25. The significance level was set at P<0.05. Results: Girls with working mothers exhibited higher empathy levels (69.43±8.75) compared to those with non-working mothers (61.77±7.68) (P<0.05). Similarly, positivity scores were higher for girls with working mothers (57.29±9.00) than those with non-working mothers (44.13±12.02) (P<0.05). Significant differences were also found in the five major personality traits so that the girls with working mothers had higher mean scores (233.1±20.40) than those with non-working mothers (183.2±20.23) (P<0.05). Conclusion: The study revealed that maternal employment may significantly influence the development of empathy, positivity, and personality traits in adolescent girls. These findings underline the potential social and psychological benefits of maternal employment, with implications for understanding adolescent developmental outcomes in the context of family dynamics. Further research is needed to explore these relationships in detail, considering additional environmental and familial variables.